The neurexin gene family regulates olfactory glomerular formation - Sung Jin Park; Namgyu Lee; I-Hao Wang; Hao-Ching Jiang; Thuyvan Luu; Takeshi Uemura; Kensuke Futai; Dohoon Kim; Evan Macosko; Paul Greer (Cell Reports)
Summary: Precise connectivity between specific neurons is essential for the formation of the complex neural circuitry necessary for executing intricate motor behaviors and higher cognitive functions. While trans interactions between synaptic surface proteins have emerged as crucial elements in orchestrating the assembly of neural circuits, the proteins involved in neuronal wiring remain largely unknown. Here, we uncover that the neurexin family of genes enables olfactory sensory neuron (OSN) axons to form appropriate connections with their mitral/tufted (M/T) cell synaptic partners within the olfactory system. Neurexins, which are differentially expressed within distinct populations of OSNs, synergistically cooperate to regulate axonal sorting to designated glomeruli. This process is facilitated through the interactions of neurexins with their postsynaptic partners, which have distinct expression patterns in M/T cells. Our findings suggest a mechanism underpinning the precise assembly of olfactory neural circuits, driven by the trans interaction between neurexins and their ligands.